Caráter stay-green: contribuições para a remoção do platô de produtividade e incremento na estabilidade de genótipos de trigo. - Luche, Henrique de Souza (2011)
The understanding of the physiological processes associated with yield and adaptation to stress conditions, as well as the application of this knowledge through breeding programs, have been appointed as key elements for the expansion of food production in the world. Among the physiological mechanisms widely discussed in the literature, the stay-green character has stood out for their carriers to give good performance as the yield, especially in restrictive environmental conditions such as drought, high temperatures occurring during the cycle and places with high incidence of certain plant pathogens. Therefore, this study aims to evaluate the consequences of delaying senescence, stay-green, in grain yield and phenotypic stability of this character in hexaploid wheat lines. The experiment was conducted in the winter season of the years 2003, 2004 and 2005 in the experimental field of the Plant Genomics and Breeding Center (FAEM / UFPel) located in the municipality of Capão do Leão. The experimental design was randomized blocks with three replicates with an observation unit of 1.8 m2. We evaluated 34 genotypes of wheat and 17 lines with them synchronized senescence, 15 the genetic constitutions bearing the stay-green character and two control elite cultivars (CD 177 and CEP 27). Observing the yield performance of stay-green and synchronized over the three years of evaluation, it is possible to establish an association among the presence of character with high yield, especially under conditions of abiotic stress factors, such as occurred in the year 2005. Analyzing the phenotypic stability parameters, the data corroborate the idea that the use of stay-green character contributes to reducing the environmental effect of the variation in the total phenotypic variation of the genotype for the traits of interest. Moreover, striking differences were seen in the degree and direction of association among the characters of genotype with normal and delayed senescence, suggesting that the choice of the selection criteria for conducting the segregating populations is very important. Therefeore, the use of character stay-green contributes positively to grain yield and phenotypic stability of this variable in hexaploid wheat lines.